Unlocking superior hydrogen oxidation and CO poisoning resistance on Pt enabled by tungsten nitride-mediated electronic modulation - Cai, Bin (2025)
Enhancing the activity and CO poisoning resistance of Pt-based catalysts for the anodic hydrogen oxidation reaction (HOR) poses a significant challenge in the development of proton exchange membrane fuel cells. Herein, we leverage theoretical calculations to demonstrate that tungsten nitride (WN) can intricately modulate the electronic structure of Pt. This modulation optimizes the hydrogen adsorption, significantly boosting HOR activity, and simultaneously weakens the CO adsorption, markedly improving resistance to CO poisoning. Through prescreening with rational design, we synthesized an efficient catalyst comprising a minimal Pt content (only 1.4 wt %) supported on the small-sized WN/reduced graphite oxide (Pt@WN/rGO). As anticipated, this catalyst showcases a remarkable acidic HOR mass activity of 3060 A gPt-1, which is approximately 11.8 times greater than that of the commercial 20 wt % Pt/C catalyst. Impressively, it maintains high activity with 98.2% retention even in the presence of 1000 ppm of CO, indicating exceptional poison resistance. Operando synchrotron radiation analyses reveal that WN harmonizes the electron state of Pt during electrochemical reactions, optimizing hydrogen adsorption/desorption dynamics. This leads to a lower peak potential of CO stripping on Pt@WN/rGO compared to that on Pt/rGO, suggesting that WN mitigates competitive CO adsorption and enhances the availability of hydrogen adsorption sites on Pt. The synergistic effect significantly accelerates HOR activity and increases antipoisoning efficacy. The assembled PEMFC demonstrates substantial tolerance to CO concentration from 10 to 1000 ppm in the H2/CO mixture.